Optimizing Fabrication of Plasma-Driven CuO Shell Over Porous Al2O3 Substrate to Meet Coating Issues - Kaentown, Sasithon; Wang, Wei Cheng; Lin, Yi Cheng; Chankitmunkong, Suwaree; Diewwanit, Onnjira; Yeung, Wing Kiu (My University, 2026)
A plasma-driven in situ conversion strategy was developed in which Cu2O nanoparticles introduced into an alkaline phosphate–hydroxide electrolyte undergo oxidative transformation to CuO within plasma micro-discharge channels during plasma electrolytic oxidation (PEO) of AA6061 aluminum alloy. The positive duty cycle was systematically varied from 10% to 40% under constant mean current density to regulate dielectric breakdown behavior, discharge energy input, and interfacial oxidation conditions. Voltage transient analysis, X-ray diffraction, field emission scanning electron microscopy, and scratch adhesion testing were employed to correlate discharge characteristics with phase evolution and coating integrity. A progressive increase in the duty cycle was found to reduce the dielectric breakdown transition voltage, promote more spatially distributed microdischarges, and facilitate charge-transfer-driven oxidation of Cu2O to CuO within the active oxide growth zone. This plasma-assisted redox mechanism enables CuO to form co-spatially with Al2O3 melting and rapid re-solidification, producing a CuO shell structure distributed over the porous alumina matrix rather than as a passively entrapped particulate phase. The resulting microstructural densification suppresses discharge-crater porosity, reduces surface roughness, and improves coating–substrate adhesion by nearly twofold relative to particle-free PEO coatings. These findings establish that duty-cycle-controlled discharge behavior provides a mechanistically grounded and dispersant-free route for fabricating CuO-modified oxide coatings with enhanced structural integration and interfacial adhesion on aluminum alloys.
Keywords: AA6061 aluminum alloy; adhesion strength; Cu2O nanoparticles; CuO composite PEO